Letter - Churchill, Victor Peter Spencer, Viscount, 1890-1973
C02-0064-001 Hotel Arvor Rue Laferriere Paris June 9th 1938 Dear Morgan I shall be in London by June 16th & would very much like to see you. Perhaps you would lunch with me Thursday June 16th or Friday 17th if you are free either of these days. Would you send me a line to P. Spencer c/o Wagon-Lits Cooks, Place de la Madeleine, Paris letting me know which day is convenient. With my kindest regards to Mrs Morgan & yourself. Very sincerely yours Churchill 292C/946/2/64